BIBLIOMETRIC ANALYSIS OF RESEARCH ON INCLUSIVE EDUCATION: A REVIEW OF PAPERS FROM THE SCOPUS DATABASE PUBLISHED IN ENGLISH FOR THE PERIOD OF 2013-2022 - Shakhnoza Tokhtiyarova; Dilbar Nurkeldieva (The Bioscan, 2024)
This study examines the trends in inclusive education research by analyzing 1836 publications from the Scopus database (2013-2022). Focusing on Social Science and Arts and Humanities subjects, we observe a consistent rise in publications, reaching a peak of 316 in 2022. The collaboration of diverse institutions worldwide, with Monash University leading, underscores the global effort in inclusive education research. Geographically, English-speaking countries dominate, supplemented by a robust European presence. This analysis offers insights into the evolving landscape of inclusive education research and provides a foundation for future investigations.